(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Objective: To evaluate the clinical and immunological characteristics of angiogenesis factors, tissue repair markers, and endothelial dysfunction in patients with diabetic foot syndrome associated with type 2 diabetes mellitus. Materials and Methods: The study included patients with type 2 diabetes mellitus with and without diabetic foot syndrome, as well as apparently healthy controls matched by age and sex. Serum concentrations of VEGF-A, IGF-1, TGF-β1, and sVCAM-1 were determined using enzyme-linked immunosorbent assay. Statistical analysis was performed using nonparametric methods. Results: Patients with diabetic foot syndrome demonstrated a more severe clinical profile characterized by a higher prevalence of obesity, arterial hypertension, cardiovascular disease, diabetic polyneuropathy, retinopathy, nephropathy, and macroangiopathy. Immunological analysis revealed decreased serum levels of VEGF-A and IGF-1 together with elevated TGF-β1 and sVCAM-1 levels. These changes were most pronounced in patients with diabetic foot syndrome and reflected impaired angiogenesis, reduced tissue reparative capacity, endothelial activation, vascular inflammation, and tissue remodeling. Conclusion: Diabetic foot syndrome in patients with type 2 diabetes mellitus is associated with a combined clinical and immunological profile characterized by suppression of angiogenesis, reduced reparative potential, endothelial dysfunction, and chronic vascular inflammation. Comprehensive assessment of VEGF-A, IGF-1, TGF-β1, and sVCAM-1 may be useful for early identification of patients at high risk for diabetic foot complications.